Pengaruh Kompetensi, Pengalaman, dan Lingkungan Kerja terhadap Kinerja Pegawai Desa - I Made Erlan Widiana; Andi Surya; Desmon Desmon; Yudhinanto Yudhinanto; Hasbullah Hasbullah; Evi Meidasari (Penerbit Goodwood, 2025)
Purpose: This study aims to determine the influence of work competence, work experience, and the environment on the performance of employees of the Restu Buana Village Office. Methodology/approach: This type of research uses quantitative methods and associative approach methods are used. The data used is primary data which requires data or information from the first source, basically we call it respondents. The analysis method used in this research is multiple linear regression analysis using SPSS version 23. Results/findings: The work competency variable affects the performance of employees of the Restu Buana Village Office. Work experience has no effect on the performance of employees of the Restu Buana Village Office. Conclusions: The study concludes that work competence, work experience, and work environment jointly have a significant effect on employee performance at the Restu Buana Village Office, with a combined influence of 92.8%. Individually, work competence contributes 26.8%, work experience 3.8%, and work environment 41.4% to employee performance. Limitations: The independent variables in this research are only work competence, work experience, and work environment as well as variables bound by employee performance. This study focuses on the employees of the Restu Buana Village Office which totals 32 people. Contribution: Because work competence, and the environment play an important role in the progress of the employees' abilities that will be developed and can provide encouragement and foster employees to be able to work independently can also foster confidence and make new work plans for employees so that performance is increasing.